Exploring rural retail food environments in South Asia: Food availability, diversity, and density of retail stores - Afrin, Zainab Bi; Choudhury, Samira; Faijul Kabir, A.N.M; Veettil, Prakashan Chellattan (International Rice Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia), a CGIAR regional integrated initiative, addresses food system challenges by delivering actionable evidence and scalable innovations in South Asia. This brief offers an overview of rural retail food environments in Bangladesh and India. The insights aim to guide policymakers in redesigning food environments to promote the availability of nutritious foods while effectively monitoring and reducing the sale of unhealthy products.